2016
DOI: 10.5194/acp-16-4043-2016
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and physical influences on aerosol activation in liquid clouds: a study based on observations from the Jungfraujoch, Switzerland

Abstract: Abstract. A simple statistical model to predict the number of aerosols which activate to form cloud droplets in warm clouds has been established, based on regression analysis of data from four summertime Cloud and Aerosol Characterisation Experiments (CLACE) at the high-altitude site Jungfraujoch (JFJ). It is shown that 79 % of the observed variance in droplet numbers can be represented by a model accounting only for the number of potential cloud condensation nuclei (defined as number of particles larger than … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 74 publications
1
22
0
Order By: Relevance
“…The black solid line represents the precipitation rate (mm h -1 ) recorded from the MeteoSwiss observation station for each 10-min interval at WFJ between 1 and 8 of March 2019. Figure 3, the observed CCN concentrations tend to be low (∽10 2 cm −3 ) even at the highest SS (0.74%), which is expected given that WFJ is a remote continental measurement site with CCN concentrations that are typical of FT continental air (Jurányi et al, 2010(Jurányi et al, , 2011Hoyle et al, 2016;Fanourgakis et al, 2019). This is again in line with the measured monthly median values of CCN (at SS=0.71%) reported by Jurányi et al is a site frequently located in the FT, sudden fluctuations in the CCN concentrations could be related to the vertical transport of freshly emitted particles (e.g., wood burning or vehicle emissions) from the valley floor in Davos.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…The black solid line represents the precipitation rate (mm h -1 ) recorded from the MeteoSwiss observation station for each 10-min interval at WFJ between 1 and 8 of March 2019. Figure 3, the observed CCN concentrations tend to be low (∽10 2 cm −3 ) even at the highest SS (0.74%), which is expected given that WFJ is a remote continental measurement site with CCN concentrations that are typical of FT continental air (Jurányi et al, 2010(Jurányi et al, , 2011Hoyle et al, 2016;Fanourgakis et al, 2019). This is again in line with the measured monthly median values of CCN (at SS=0.71%) reported by Jurányi et al is a site frequently located in the FT, sudden fluctuations in the CCN concentrations could be related to the vertical transport of freshly emitted particles (e.g., wood burning or vehicle emissions) from the valley floor in Davos.…”
Section: Resultssupporting
confidence: 52%
“…Given the importance of droplet number for the radiative cloud properties and microphysical evolution of Alpine MPCs, it is essential to understand the main aerosol and dynamics properties that drive droplet formation. A limited number of studies exist that discuss this very important topic, focusing though on liquid-phase clouds (Hammer et al, 2014(Hammer et al, , 2015Hoyle et al, 2016). Hoyle et al (2016) demonstrated that 79% of the variance in droplet number observed in warm tropospheric clouds formed over the high-altitude research station of Jungfraujoch (3450 m a.s.l.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same data can be used to derive the direct sensitivity of cloud to aerosol perturbations for model and satellite evaluation 72,79 , and to understand the relative contribution of aerosol and dynamic parameters in the variability of droplet formation 80 .…”
Section: Usage Notesmentioning
confidence: 99%
“…Table 1 also lists the collection efficiency (CE) of each mass spectrometer. The CE depends on the transmission of particles into the instrument and their chemical composition and is hence an instrument and site-specific factor (Huffman et al, 2005;Middlebrook et al, 2012).…”
Section: Measurement Sites and Instrumentationmentioning
confidence: 99%